(untitled) (Ágora Journal, 2026)
This paper aims to assess the validity of Wagner Mancuso’s (2007) thesis regarding the political strength of industrial business during the New Republic. To this end, we analyze some aspects of the reorganization of industrial business around the CNI (National Council of Nationalities), the profile of the class elite and the political strength of industrial business throughout the New Republic, and, finally, the problem of deindustrialization vis-à-vis financial dominance. We note that the institutional legacies left by Fernando Henrique Cardoso (1995-2002), the macroeconomic tripod and the floating exchange rate, act as a kind of straitjacket that simultaneously limited the strengthening of industrial business as a class and the development-inspired project of the Workers’ Party. Thus, based on the data analyzed, we agree with Pochmann (2016) regarding the problem of deindustrialization in Brazil and the hegemony of finance capital as a limiting factor for industrialism in Brazil.